Association of behavioral, socioeconomic factors and smoking with increased blood pressure among adoloscents aged 13-17 in Manila High School - 4 0 16; 5
Hypertension is the leading single risk factor for deaths worldwide. It is an emergent health problem among children and adolescents that is often overlooked by physicians. The extent to which health behaviour and socioeconomic factors were linked to blood pressure has been examined in this study. Also, exposure of adolescents from smoking was associated with prevalence of hypertension.
Keywords: 2 -- 0; 6; 20; 20; 2